Communications between Mitochondria, the Nucleus, Vacuoles, Peroxisomes, the Endoplasmic Reticulum, the Plasma Membrane, Lipid Droplets, and the Cytosol during Yeast Chronological Aging - Dakik, Pamela; Titorenko, Vladimir I. (Frontiers in Genetics, 2016)
Studies employing the budding yeast Saccharomyces cerevisiae as a model organism have provided deep insights into molecular mechanisms of cellular and organismal aging in multicellular eukaryotes and have demonstrated that the main features of biological aging are evolutionarily conserved. Aging in S. cerevisiae is studied by measuring replicative or chronological lifespan. Yeast replicative aging is likely to model aging of mitotically competent human cell types, while yeast chronological aging is believed to mimic aging of post-mitotic human cell types. Emergent evidence implies that various organelle-organelle and organelle-cytosol communications play essential roles in chronological aging of S. cerevisiae. The molecular mechanisms underlying the vital roles of intercompartmental communications in yeast chronological aging have begun to emerge. The scope of this review is to critically analyze recent progress in understanding such mechanisms. Our analysis suggests a model for how temporally and spatially coordinated movements of certain metabolites between various cellular compartments impact yeast chronological aging. In our model, diverse changes in these key metabolites are restricted to critical longevity-defining periods of chronological lifespan. In each of these periods, a limited set of proteins responds to such changes of the metabolites by altering the rate and efficiency of a certain cellular process essential for longevity regulation. Spatiotemporal dynamics of alterations in these longevity-defining cellular processes orchestrates the development and maintenance of a pro- or anti-aging cellular pattern.